Sterol 14,15 reductase (erg-3) mutations switch the phenotype of Neurospora crassa from sensitivity to the tomato saponin alpha-tomatine to sensitivity to the pea phytoalexin pisatin - Saswati Sengupta; T. Bhavani Prasanna; D. P. Kasbekar (Fungal Genetics Reports, 1995)
The erg-3 gene of Neurospora crassa encodes the sterol biosynthetic enzyme sterol 14,15 reductase. This was first suggested by the finding that the erg-3 mutant strain accumulated precursors of ergosterol that retain the double bond between carbons 14 and 15 in the sterol C ring (Ellis et al. 1991, J. Gen. Microbiol. 137:2627-2630). Consistent with this result, cloning and sequencing of erg-3 revealed that the encoded protein is highly homologous to the sterol 14, 15 reductase of yeast (Papavinasasundaram and Kasbekar, 1994, J. Genet. 73:33-41). The cloning of erg-3 (and of erg-1, the structural gene encoding sterol 8,7 isomerase) was made possible by the discovery that their mutants are sensitive to the pea phytoalexin pisatin (Papavinasasundaram and Kasbekar, 1993, J. Gen. Microbiol. 139:3035-3041).